Association between early spontaneous abortion and homocysteine metabolism - Lei, Fangliang; Zhang, Lili; Wang, Li; Wu, Wentao; Wang, Fei (Frontiers in Medicine, 2024)
Objective The purpose of this study is to explore the effects of homocysteine (HCY) metabolism and related factors on early spontaneous abortion. Methods We conducted a hospital-based case–control study and included a total of 500 cases and 1,000 controls in Shaanxi China. Pregnant women waiting for delivery in the hospital were interviewed to report their characteristics and other relevant information during pregnancy. The unconditional Logisitic regression model was applied to assess the association between early spontaneous abortion and HCY metabolism and related factors. The multiplicative model was applied to assess the effects of interaction of HCY metabolism and related factors on early spontaneous abortion. The logit test method of generalized structural equation model (GSEM) was used to construct the pathway diagram of HCY metabolism and related factors affecting early spontaneous abortion. Results Folic acid supplementation and adequate folic acid supplementation during periconception were the protective factors of early spontaneous abortion (OR = 0.50, 95% CI: 0.38–0.65; OR = 0.44, 95% CI: 0.35–0.54). The serum folate deficiency, higher plasma HCY in early pregnancy, the women who carried the MTHFR 677TT genotype were the risk factors of early spontaneous abortion (OR = 5.87, 95% CI: 1.53–22.50; OR = 2.94, 95% CI: 1.14–7.57; OR = 2.32, 95% CI: 1.20–4.50). The women’s educational level and maternal and child health care utilization affected the occurrence of early spontaneous abortion by influencing the folic acid supplementation during periconception. The folic acid supplementation during periconception affected the occurrence of early spontaneous abortion by influencing the level of serum folate or plasma HCY in early pregnancy. The maternal MTHFR 677 gene polymorphism affected the occurrence of early spontaneous abortion by influencing the level of serum folate in early pregnancy. In terms of the risks for early spontaneous abortion, there was multiplicative interaction between higher plasma HCY in early pregnancy, serum folate deficiency in early pregnancy and maternal MTHFR 677TT genotype (OR = 1.76, 95% CI: 1.17–4.03), and there was multiplicative interaction between higher plasma HCY and serum folate deficiency in early pregnancy (OR = 3.46, 95% CI: 2.49–4.81), and there was multiplicative interaction between serum folate deficiency in early pregnancy and maternal MTHFR 677TT genotype (OR = 3.50, 95% CI: 2.78–5.18). The above interactions are all synergistic. The occurrence risk of early spontaneous abortion was significantly increased if multiple factors existed at the same time. Conclusion Our study is the first time to construct the pathway of HCY metabolism and related factors affecting early spontaneous abortion, and provides a comprehensively new idea to prevent and reduce the occurrence of spontaneous abortion.